Beyond Coding and Control: Leakage, Categorization and Blocking in the Definition of the English Subject - Javier Martín Arista (Miscelánea: A Journal of English and American Studies)
This paper offers a non-intuitive definition of the English subject by discussing Keenan's coding and control properties and by contending that leakage, blocking properties (co-referentiality, omission of the relative and question target) and categorization must also be taken into account in the definition of this grammatical function. The consideration of leakage and blocking properties allows for a cross-theoretical approach to this syntactic phenomenon that may modify Keenan's hierarchy of subject properties and the hierarchy of syntactic functions of Keenan and Comrie.